1979
DOI: 10.1246/bcsj.52.1657
|View full text |Cite
|
Sign up to set email alerts
|

α,β-Unsaturated Carboxylic Acid Derivatives. XVII. The Facile Synthesis of Ethyl α-Azido-α-alkenoates and Reduction to Ethyl α-Amino-α-alkenoates

Abstract: Several pathways leading to ethyl α-azido-α-alkenoates (8) by the β-elimination to ethyl α-azido-β-substituted (hydroxy-, acetoxy-, or mesyloxy)-alkanoates with NaN3 or Et3N have been examined. The optimized procedure, in combination with subsequent reduction provides a general synthetic route to α-amino-α-alkenoic acid esters (9). The configuration of 8 and 9 have been shown to be of (Z)-geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Brominations of related compounds with N-bromosuccinimide (NBS) were reported to be substantially slower. [28] Our preliminary estimation, made by NMR, of the rates of bromination of benzylideneacetone (1a) in [D 4 ]MeOH with NBS and with NBSac revealed that the reactivity of the latter is approximately 400 times that of the former. Bromination of benzylideneacetophenone (1b) and methyl (E)-cinnamate (1f) with NBS in 10 % excess required approx.…”
Section: Resultsmentioning
confidence: 98%
“…Brominations of related compounds with N-bromosuccinimide (NBS) were reported to be substantially slower. [28] Our preliminary estimation, made by NMR, of the rates of bromination of benzylideneacetone (1a) in [D 4 ]MeOH with NBS and with NBSac revealed that the reactivity of the latter is approximately 400 times that of the former. Bromination of benzylideneacetophenone (1b) and methyl (E)-cinnamate (1f) with NBS in 10 % excess required approx.…”
Section: Resultsmentioning
confidence: 98%